Major Insect Pest Management in Paddy (Oryza sativa L.): A Review - Dhirendra Pratap Singh (Public Health, 2026)
Rice (Oryza sativa L.) is a staple food crop supporting more than half of the global population. However, its productivity is severely constrained by insect pests, which cause significant yield losses at different crop growth stages. More than 100 insect species infest rice, but only about 15–20 species are of economic importance. Major pests include stem borers, planthoppers, leaf folders, gall midge, and gundhi bug. Effective pest management requires an integrated approach combining cultural, biological, mechanical, and chemical methods. This review highlights major insect pests of rice, their damage symptoms, and sustainable management strategies with emphasis on Integrated Pest Management (IPM).